Integrated advertising, promotion, and marketing communications - Clow, Kenneth E.; Baack, Donald (Upper Saddle River, N.J. : Pearson Prentice Hall, 2007)
Using a hands-on approach, this text shows students how to develop a complete integrated marketing communications programme. It incorporates Internet exercises and a 'Building an IMC Campaign' project, with free 'Advertising Plan Pro' software.
Integrated marketing communications -- Corporate image and brand management -- Buyer behaviors -- Promotions opportunity analysis -- Advertising management -- Advertising design: theoretical frameworks and types of appeals -- Advertising design: message strategies and executional frameworks -- Advertising media selection -- Trade promotions -- Consumer promotions -- Personal selling, database marketing, and customer relationship management -- Public relations, sponsorship programs, and regulations -- Internet marketing -- IMC for small businesses and entrepreneurial ventures -- Evaluating an integrated marketing program.
Includes bibliographical references.
Keywords: Communication in marketing; Advertising; Reclame